“VOCATIONALLY ORIENTATED CULTURE AND LANGUAGE IN NEED”: THE OPPORTUNITY TO EDUCATE STATE BORDER GUARDS IN CULTURE AND LANGUAGE - Zuzevičiūtė, Vaiva; Pranevičienė, Birutė; Vasiliauskienė, Violeta (Border Security and Management, 2018)
The article introduces the project “Vocationally Orientated Culture and Language in Need” (financed by the European Commission) which aims to help law-enforcement officers to develop competencies in linguistic and cultural diversity that is facing (or will be facing) them in the communities they serve. This is a vivid illustration of the prognostic modelling.